Characterization of β-agarase produced by Alteromonas macleodii BC7.1 and its oligosaccharide products - Dewi Seswita Zilda; Gintung Patantis; Ariyanti S. Dewi; Tiara S. Khatulistiani; Mada Triandala Sibero; Jiang Li (Case Studies in Chemical and Environmental Engineering, 2024)
Marine associated-bacteria is an excellent source for novel enzymes. The quest to find new agarases with unique properties for industrial application is continually growing. Agarase hydrolyzed agar to oligoagar for broader applications. Herein, we report the production of β-agarase from Alteromonas macleodii BC7.1, a marine sediment bacteria collected in Barra Cadi Island, South Sulawesi, Indonesia. The enzyme production was optimal using a medium containing 0.4 % of agar after 48 h incubation. The enzyme has an optimum activity at 45 °C, pH 7–8 and was stable for 12 h incubation. Agarase BC7.1 (Aga-BC7.1) was resistant to most ions (except Zn and Mn), denaturing agents and chemicals. The Km and Vmax values were 18 mg/mL and 100 U/mg, respectively. The molecular size of agarase in its native condition was 220 kDa. Based on α-glucosidase inhibition activity indicated that oligosaccharides can be produced within 8–24 hours using 0.3–0.5 % (w/v) substrate, at 30–37 °C, with 50 mM Tris-HCl buffer at pH 7.0 and various types of agar. The HPLC analyses of the hydrolysis products confirmed the presence of neoagarooligosaccharides (NAOS), neoagaro-biose (NA2), -tetraose (NA4), and -hexose (NA6). A mixture of oligosaccharides with a major content of NA2 exhibits the highest α-glucosidase inhibition activity compared to crude oligosaccharides and other fractions. This study thus highlights the potency of β-agarase from A. macleodii for industrial application.